Azospirillum brasilense via fertilizante organomineral coinoculado com Bradyrhizobium japonicum na cultura da soja - Barros, Fernanda Carvalho (2019)
The symbiosis between nitrogen-fixing bacteria and legumes, such as soybean, forms the most important biological nitrogen fixation system and it has been successfully used, making possible a very significant saving in nitrogen fertilizers. The objective of this work was to evaluate the effect of the association between Bradyrhizobium japonicum and Azospirillum brasilense on soybean crop. Seed germination and seedling growth tests were installed in the laboratory according to the requirements of the Rules for Seed Analysis. The experimental design was in randomized blocks with 5 replicates and 4 treatments (B. japonicum; A. brasilense; B. japonicum + A. brasilense and control). Germination test evaluations were performed by counting the number of normal (strong and weak), abnormal (deformed and decayed) and dead seedlings. For the seedling growth test, it was evaluated the shoot length of seedlings, the radicle length of seedlings and the dry masses of shoot and rootlets. Two experiments were also carried out in a greenhouse, the first one using 5 L plastic pots at Fazenda Capim Branco - UFU, and the second using 8 L seedlings at Campus Glória - UFU. The experiments were conducted in a randomized block design in a 4 × 2 +1 factorial scheme, corresponding to four doses of a commercial product containing A. brasilense (0, 100, 200 and 300 mL 50 kg-1 of soybean seeds), with and without inoculation of commercial product with B. japonicum at a dose of 100 mL ha-1 and an additional treatment corresponding to the control (without inoculants or fertilizer), totaling nine treatments. Experiment 1 were conducted with four replicates and two pots per plot and experiment 2 was conducted with five replicates, six bags of molt per plot. The cultivar AS 3680 IPRO was used. Phenometric evaluations, antioxidant metabolism, chlorophyll A and B analyzes, chemical analyzes and productivity indicators were performed. The average germination, length, shoot dry mass and radicle obtained did not present significant difference. In experiment 1, isolated inoculation with A. brasilense showed increases for AP and AF variables. In experiment 2, the bacterium A. brasilense, in general, promoted physiological protection to the plants. The use of Bradyrhizobium japonicum and Azospirillum brasilense, inoculated alone or in co-inoculation, did not interfere with germination and seedling growth of the tested soybean cultivar, but conferred protection to the plants against stress, which was not reflected in improvements in productivity indicators.